Evaluasi Kinerja Perusahaan Keagenan Kapal pada Kegiatan Operasional di Area Labuh Muara Kaman KM. 99 hingga Jetty Terminal Tambatan Kalimantan Timur - Fadillah, Ardi; Dekanawati, Vivid; Prasaja, Mahendra Galih; Kusuma, Ade Chandra; Pratama, Himawan Aditya; Handojo, Budi (Majalah Ilmiah Gema Maritim, 2025)
The shipping industry is a sector that plays a vital role in the Indonesian economy, and shipping agency companies engaged in shipping activities are responsible for managing and coordinating activities to ensure efficient and effective operations. This study aims to measure the performance of shipping agencies based on ship waiting time and approach time. The research approach uses a quantitative method, namely analyzing descriptive statistical data. The sample in this study was the total number of visits by shipping agency companies over a six-month period, from June to November 2023. Data collection techniques used documentation of waiting time and approach time reports. The results of this study indicate that the Company's Performance measurement in Waiting Time is very good, with an average value lower than the time standard set by the agency company. This analysis was conducted for each six-month period, from June to November 2023. Furthermore, the results of the Company's Performance analysis in Approach Time are good, with an average value lower than most of each period within the six-month Approach Time period. The overtime in September, which exceeded the standard time set by the company's agency by 2.05 hours (two hours and five minutes), was caused by the ebb and flow of the river, forcing ships to wait for the river's water level to return to the jetty, delaying coal loading activities.